The role of mobile shopping in customer brand identification to increase repurchase intention - Putra, Edy Yulianto; Ihza, Nurul; Aliandrina, Dessy (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study aims to analyze the influence of mobile shopping, brand experience, and shopping enjoyment on customer brand identification and repurchase intention in local fashion brands. It is proposed to address a gap where prior research overlooks these factors' interplay for Indonesian brands, focusing instead on international contexts or price/promotions. A total of 312 respondents from Batam City participated in this study. Quantitative and associative approach design is applied in this study, in order to measure the quantity of data with relevant statistical procedures, especially with the SEM-PLS. The results of the study indicate that the use of mobile shopping is not significant to boost customer brand identification. On the contrary, positive consumer experience with the brand and shopping pleasure have been shown to influence customer brand identification. Strong brand identification significantly increases repurchase intention. This research is expected to provide a new contribution to the literature on consumer behavior in the fashion industry, particularly in the context of mobile shopping. This research provides practical guidance for marketers and local fashion brands in designing effective marketing strategies, especially in improving a pleasant shopping experience, creating a positive brand experience, and utilizing the mobile shopping potential to increase purchasing interest.